Motivation and Action - Heckhausen, Jutta; Heckhausen, Heinz (Springer, 2018)
This is the third English edition of Motivation and Action, an extensively revised version of the second English edition and fifth German edition, with four entirely new chapters. All chapters have been updated to incorporate current research trends and findings, while new chapters on the motivation of developmental regulatory behavior as well as the applied fields of school and college, workplace, and sports were added. The chapters on the affiliation motive, the power motive, and goals were completely rewritten by new authors. Each chapter comes with an individual list of references, allowing instructors to use them separately for their courses. In addition, the Springer website for the book will provide useful materials for students and instructors alike, including a glossary with key terms. The first English edition of Motivation and Action, based on the second German edition, was written by Heinz Heckhausen, who passed away on October 30, 1988. Springer and I agreed that a revised edition of this influential textbook on motivational psychology was needed. There have been many exciting and important conceptual and empirical innovations since the second English edition published in 2008, for example, in the research fields of volition and sequential phases of behavioral regulation, two perspectives that Heinz Heckhausen already discussed in the second edition (especially in Chaps. 6 “Volition” and 15 “Extended Perspectives”). Additionally, there have been important contributions to the study of the differences between and interaction of implicit versus explicit motives, as well as motivational and behavioral influences on development over the lifespan. It would be a Herculean task to provide a comprehensive overview of all these developments and to survey the field of motivation psychology in its full range and complexity. No single scientist could hope to follow in Heinz Heckhausen’s footsteps and accomplish this task alone. A collaborative approach was clearly called for, and a look at the ranks of Heinz Heckhausen’s students—and their students— shows that almost every subdomain of motivation psychology is represented by one or several renowned researchers. This new edition of Motivation and Action was only possible with the support of these scholars as authors. This book thus represents the intellectual legacy of Heinz Heckhausen in two respects. First, it shows how Heckhausen’s approach to motivation psychology has been further developed and refined and that, while much has been retained, there have also been some important changes. Second, the book’s chapters have been written by Heinz Heckhausen’s intellectual heirs: by members of his research groups in Bochum and Munich and their students and by myself, his daughter.